Neurological complication of non Hodgkin lymphoma in childhood: Experience from a single center in Turkey - Köse, Doğan; Paksoy, Yahya; Köksal, Yavuz; Ünal, Ekrem (Springer, 2014)
Lymphomas are the third most common childhood malignant disease after leukemia and central nervous system (CNS) tumors. Early diagnosis of these complications will reduce mortality and morbidity. In this study we aimed to review the neurological complications of childhood non Hodgkin Lymphoma (NHL). Forty four children with NHL between 2006 and 2012 were investigated retrospectively and 14 cases with neurological complications were identified. The most common symptom was alteration of the consciousness (10 patients, 71.4 %) followed by convulsion (5 patients, 35.7 %), and hallucination (4 patients, 28.5 %); headache, eye pain, neurogenic bladder, speech disability and facial paralysis, and hemiplegia, were less common and each of them was seen in 1 (7.1 %) of the patients. The neurological complications were mostly seen in children with precursor T lymphoblastic lymphoma followed by anaplastic large cell lymphoma. The complications were secondary to medications (Eight patients) infection (two patients); CNS relapse (two patients); or CNS involvement of the primary disease (two patients). Chemotherapy-related neurologic complications were secondary to intrathecal methotrexate, l-asparaginase, vincristine, and ifosfamide Advanced disease and PTLL subtype can be suggested as predictors of neurological complication. The survival rates of neurological complications are fairly good unless it is secondary to involvement of the primary disease. In patients with drug-induced neurological complications, the treatment can be safely re-administered after controlling the neurological complications. Therefore, clinicians managing children with NHL must be informative about neurological complications.
WOS: 000334055500013
PubMed ID: 23989474
Keywords: Children; Non Hodgkin Lymphoma; Neurological Complication